Insights into the adsorptive application of solvent assisted hydrothermal carbonization products - Tamara Samer Alomar (22827269) (2025)
Solvent-assisted hydrothermal carbonization or solvothermal carbonization (STC) is a process involving the conversion of biomass into carbonaceous materials (solvochar) with the presence of a solvent. Unlike traditional hydrothermal carbonization STC operates at lower temperatures and uses solvents rather than water. The types of solvents that are commonly reported in literature are organic and inorganic solvents, ionic liquids, and deep eutectic solvents. Solvochar has shown high effectiveness in adsorbing pollutants in both liquid phases (e.g., dyes, organic compounds, and heavy metals) and gaseous phases (e.g., CO₂). Adsorption studies suggest monolayer adsorption in most cases, based on the Langmuir isotherm, while kinetic studies highlight chemisorption via pseudo-second-order models. For gaseous applications, solvochar can be thermally regenerated, while liquid-phase applications require chemical eluents. These properties enable solvochar to be reused for multiple cycles, where solvochar could be regenerated for approximately 5 cycles using chemical eluents in liquid phase and 10 cycles thermally in gas-phase applications. Future studies should work towards developing continuous scaled-up processes, the use of real wastewater, as well as techno-economic analysis to ensure the cost effectiveness and applicability of solvochar on a commercial scale. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.117464